Fast Eccentric Movement Tempo Elicits Higher Physiological Responses than Medium Eccentric Tempo in Ice-Hockey Players - Gepfert, Mariola; Trybulski, Robert; Stastny, Petr; Wilk, Michał (International journal of environmental research and public health, 2021)
BACKGROUND: Resistance training is a significant part of ice-hockey players' conditioning, where optimal loading should ensure strength development and proper recovery. Therefore, this study aimed to compare the acute physiological responses to fast and medium movement tempo resistance exercises in ice-hockey players. METHODS: Fourteen ice-hockey players (26.2 ± 4.2 years; 86.4 ± 10.2 kg; squat one repetition maximum (1RM) = 130.5 ± 18.5) performed five sets of the barbell squat and barbell bench press at 80% 1RM until failure in a crossover design one week apart using either 2/0/2/0 or 6/0/2/0 (eccentric/isometric/concentric/isometric) tempo of movement. The blood samples to evaluate the concentration of cortisol, testosterone, insulin-like growth factor 1 (IGF-1), and growth hormone (hGH) were taken before exercise, 3 min after the last set of the squat exercise, 3 min after the last set of the bench press exercise, and after 30 min of recovery. RESULTS: The 2/0/2/0 tempo resulted in a higher number of repetitions (p < 0.001) and lower time under tension (p < 0.001) in the squat and bench press exercises compared to the 6/0/2/0 movement tempo. The endocrine responses to exercise were significantly higher during the 2/0/2/0 compared to the 6/0/2/0 movement tempo protocol for IGF-1, hGH, and cortisol (p < 0.01). There were no differences in testosterone responses between exercises performed with fast and medium movement tempos. CONCLUSION: Fast eccentric tempo induced higher cortisol, IGF-1, and hGH responses compared to the medium tempo. Therefore, fast eccentric movement tempo seems to be more useful in eliciting training stimulus than medium eccentric tempo during resistance training in ice-hockey players. However, future studies are needed to confirm our findings.
Keywords: kosterní svaly; klinické křížové studie; conditioning; Testosterone; Hydrocortisone; Humans; Hockey; testosteron; growth hormone (hGH); insulin-like growth factor 1 (IGF-1); Muscle, Skeletal; hydrokortison; hokej; svalová síla; Human Growth Hormone; resistance training; Resistance Training; odporový trénink; Cross-Over Studies; cortisol; lidský růstový hormon; lidé; Muscle Strength; testosterone